2022
DOI: 10.1002/2475-8876.12303
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into urban heat mitigation by adopting local climate zones and land surface temperatures in the Tokyo prefecture

Abstract: This study aimed to investigate urban forms susceptible to heightened heat intensities in the Tokyo Prefecture in Japan. Adopting Landsat 8 data at a pixel resolution of 100 m, local climate zones (LCZ) were identified. LCZs contain urban forms which are primarily defined by building compactness and height. Daytime spatial distribution of land surface temperatures (LST) was provided by MODIS 100 m resolution data from 2013 to 2021. Median LSTs for compact and super high‐rise, high‐rise, mid‐rise, and low‐rise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…Heavy industry type had some overlapped ranges with open mid-rise type and open low-rise type. Through GEP, it was found that the heavy industry type exists only in the areas neighboring Tokyo, such as Kawasaki, Yokohama, and Chiba, but not in Tokyo itself, which is consistent with previous studies [86,98]; hence, heavy industry type was not defined in Tokyo in this study.…”
Section: Lcz Classification Using the Wudapt L0 Methodssupporting
confidence: 90%
See 2 more Smart Citations
“…Heavy industry type had some overlapped ranges with open mid-rise type and open low-rise type. Through GEP, it was found that the heavy industry type exists only in the areas neighboring Tokyo, such as Kawasaki, Yokohama, and Chiba, but not in Tokyo itself, which is consistent with previous studies [86,98]; hence, heavy industry type was not defined in Tokyo in this study.…”
Section: Lcz Classification Using the Wudapt L0 Methodssupporting
confidence: 90%
“…LCZ land cover types were defined through the description of each LCZ land cover type (Figure A1) and satellite images in GEP. Bush & scrub type (LCZ C) and bare soil or sand type (LCZ F) were not found in Tokyo, consistent with the previous study [86,98], so they were not defined in Tokyo. Dense trees type (LCZ A) and shrubs & bushes type (LCZ C) were located outside the administrative boundaries of Shanghai [99], so they were not defined in Shanghai.…”
Section: Lcz Classification Using the Wudapt L0 Methodssupporting
confidence: 83%
See 1 more Smart Citation